Etiology of nosocomial infections in intensive care patients in German hospitals: An analysis of trends between 2008 and 2022 - Petra Gastmeier; Axel Kola; Frank Schwab; Michael Behnke; Christine Geffers (Elsevier, 2024)
Purpose: Data from the intensive care component of the German hospital infection surveillance system (KISS) was used to investigate the epidemiology of pathogens responsible for the most frequent device-associated infections and their development over time. Method: The 10 most common pathogens were identified for ventilator-associated lower respiratory tract infections (VALRTI), catheter associated urinary tract infections (CAUTI), and central venous catheter associated bloodstream infections (CVC-BSI). The development over time was analyzed based on three five-year time periods: 2008-2012, 2013-2017, 2018-2022. Results: Data from 1425 ICUs were included together with 121,762 device-associated infections with 138,299 isolated pathogens. A remarkable and significant increase in the frequency of Klebsiella spp. was found for VALRTI, that was almost twice as high during 2018-2022 compared to 2008-2012. For CAUTI, there was a significant increase of all Enterobacterales with the most prominent increase in Klebsiella spp. With regard to CVC-BSI, the situation for coagulase-negative staphylococci and E. coli was relatively stable; while there was a significant increase in Enterococcus spp. and Klebsiella spp. and a decrease in S. aureus. Conclusion: Knowledge about the current frequency of pathogens responsible for nosocomial infections in intensive care units is important for guiding empirical antimicrobial therapy. Data from national nosocomial infection surveillance systems can provide relevant information about the development of pathogens.